Disruptive Innovation and the Future of Digital Agriculture: A Systematic Review of New Technologies in Agricultural Marketing Channels - Usmiati; Said, Laila Refiana; Rifani, Ahmad; Firdaus, Muhammad Riza; Fitriadiansyah, Ricky (Archives of Business Research, 2025)
This article systematically reviews disruptive innovations transforming digital marketing channels within the agricultural sector. Utilising a Systematic Literature Review (SLR) methodology, it critically examines the application of emerging technologies such as artificial intelligence (AI), big data analytics, blockchain, and the Internet of Things (IoT) that enhance the efficiency, personalisation, and automation of agricultural marketing platforms. These technologies empower agribusinesses to optimise customer engagement, streamline supply chains, and deliver tailored experiences to farmers and consumers alike. Despite the considerable advantages, the review highlights persistent challenges, including data privacy concerns, integration complexities across diverse marketing channels, and digital skill gaps among stakeholders in agriculture. This study offers comprehensive insights into how disruptive technologies are reshaping the future of digital agriculture marketing and recommends strategic approaches for agribusinesses to address these challenges effectively. Furthermore, it identifies critical research gaps, suggesting avenues for future inquiry encompassing theoretical frameworks, methodological advancements, and contextual applications within digital agricultural marketing.